Neurodegeneration of Drosophila drop-dead mutants is associated with hypoxia in the brain. - Kim, J.Y.; Jang, W.; Lee, H.W.; Park, E.; Kim, C. (Genes, Brain, and Behavior, 2012)
The Drosophila drop-dead (drd) mutant undergoes massive brain degeneration, resulting in sudden death. drd encodes a multi-pass membrane protein possessing nose resistant to fluoxetine (NRF) and putative acyltransferase domains. However, the etiology of brain degeneration that occurs in drd mutant flies is still poorly understood. Herein, we show that drd neurodegeneration may be because of an oxygen deficit in the brain. We found that DRD protein is selectively expressed in cells secreting cuticular and eggshell layers. These layers exhibit blue fluorescence upon UV excitation, which is reduced in drd flies. The drd tracheal air sacs lacking blue fluorescence collapse, which likely contributes to hypoxia. Consistently, genes induced in hypoxia are up-regulated in drd flies. Feeding of anti-reactive oxygen species agents partially rescue the drd from sudden death. We propose that drd flies can provide a non-invasive animal model for hypoxia-induced cell death.